Trends of Fast Food Intake among Female College Students in Banke District (OCEM Journal of Management, Technology & Social Sciences, 2024)
Fast food, characterized by its quick preparation and low nutritional value, often contains high levels of fat, salt, sugar, and calories. This study aims to examine the correlation between the socio-demographic attributes of female college students and their fast food consumption patterns. Employing a cross-sectional research design, a total of two hundred and eighty-six (N= 286) respondents were selected through a random sampling process from four distinct colleges located in the Banke district. The findings of the study reveal that a significant majority of 83.6% of the respondents engage in fast food consumption, with 38.5% opting for solid food choices and 70.3% preferring liquid fast food options. Furthermore, 70.3% of the respondents exhibit a preference for packaged fast foods. In terms of timing, 45.1% consume fast food during the afternoon, with the least number of respondents consumed fast food during the night. In relation to frequency, 28% of the participants report consuming fast food 2 to 3 times daily, while a smaller percentage indulge in fast food consumption twice a day. Notably, this research establishes a noteworthy association between age, religion, and the educational backgrounds of respondents’ fathers and mothers with their fast food consumption habits. In contrast, the study does not find a significant association between various types of fast food consumption and the caste of the sampled students. Consequently, it underscores the importance of raising awareness about the potential health risks associated with fast food consumption, emphasizing the need for targeted initiatives to reduce the prevalence of such dietary choices among college students.